Evaluation of Sulfated Polysaccharides from the Brown Seaweed Dictyopteris Justii as Antioxidant Agents and as Inhibitors of the Formation of Calcium Oxalate Crystals - Karoline Rachel Teodosio Melo; Rafael Barros Gomes Camara; Moacir Fernandes Queiroz; Arthur Anthunes Jacome Vidal; Camila Renata Machado Lima; Raniere Fagundes Melo-Silveira; Jailma Almeida-Lima; Hugo Alexandre Oliveira Rocha (Molecules, 2013)
Oxalate crystals and other types of crystals are the cause of urolithiasis, and these are related to oxidative stress. The search for new compounds with antioxidant qualities and inhibitors of these crystal formations is therefore necessary. In this study, we extracted four sulfated polysaccharides, a fucoglucoxyloglucuronan (DJ-0.3v), a heterofucan (DJ-0.4v), and two glucans (DJ-0.5v and DJ-1.2v), from the marine alga Dictyopteris justii. The presence of sulfated polysaccharides was confirmed by chemical analysis and FT-IR. All the sulfated polysaccharides presented antioxidant activity under different conditions in some of the in vitro tests and inhibited the formation of calcium oxalate crystals. Fucan DJ-0.4v was the polysaccharide that showed the best antioxidant activity and was one of the best inhibitors of the crystallization of calcium oxalate. Glucan DJ-0.5v was the second most potent inhibitor of the formation of oxalate crystals, as it stabilized dehydrated oxalate crystals (less aggressive form), preventing them from transforming into monohydrate crystals (more aggressive form). The obtained data lead us to propose that these sulfated polysaccharides are promising agents for use in the treatment of urolithiasis.